Where do Babies Come from? Parent-Child Communication about Sex Education - Aisyah Durrotun Nafisah; Ahmad Labib; Nely Irnik Darajah; Bisri Purwanto; Nunung Dwi Setiyorini; Dewi Hajar Windi Antika (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Sex education for early childhood is very important to protect children from unwanted things in the future. The purpose of this research is to find out how parent-child communication is in sex education. The stages are in accord-ance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIS-MA). This study uses the systematic literature review (SLR) method with reference to 10 valid articles published in the last 10 years with years of publication between 2014 and 2023. The results of the literature show that although parents in this study are aware of the importance of providing information about sex education, people's communication parent-child about sex education is rare. This is because the taboo culture is still strong. In addition, parents do not understand sex education in a broad sense so that it can be taught to children from an early age. Parents lack confidence in discussing sex education for their children and do not facilitate children's curiosity about the world of sexuality. There needs to be a reorientation of parents to communicate better with their children, and start discussions about sex education.